Study on the Electrochemical Delamination and Corrosion Resistance of the Loose Layer Formed by Micro-Arc Oxidation on TA2 Titanium Alloy - YANG Yifan, GAO Jianping, WANG Xing, FAN Ruijun (Cailiao Baohu)
In order to address the issue of spalling failure of the loose outer layer of conventional titanium alloy micro-arc oxidation (MAO)coatings to delaminate in corrosive environments，a controllable electrochemical-corrosion delamination process was implemented in an ClH4NO solution.By regulating the corrosion voltage and spalling time， the loose layer of a TA2 MAO coating was selectively removed， and the phase composition， micromorphology， film thickness and corrosion resistance of the coating were examined before and after peeling of the loose layer.Results showed that the thickness of the dense coating obtained after the loose layer was peeled off by electrochemical corrosion was about 1/2 of that of the coating before peeling.The dense coating primarily composed of TiO2 and Ti2O3.Its surface displayed a pit-like corrosion morphology without discernible cracks or through-pores.Both the peeling depth and the degree of porous-layer removal increased with rising voltage and extended peeling time， with voltage exerting the greater influence.This electrochemical corrosion peeling process retained the internal structure of the dense layer while modifying its surface topography，thereby enhancing its corrosion resistance.The self-corrosion current density of the dense layer was reduced by up to two orders of magnitude， reaching a minimum of 4.819×10－9 A/cm2.Removal of the loose MAO layer eliminated numerous corrosion-failure sites and markedly improved the overall anti-corrosive performance of the coating.